Terminological Issues of Sanitary-Epidemiological Welfare Provision Both in Russia and on the Global Scale - A. E. Shiyanova; V. P. Toporkov; V. Yu. Smolensky (Проблемы особо опасных инфекций, 2013)
Discussed is the build-up of a term “sanitary protection of the territories”. Regardless of commonly accepted definition of sanitation as a discipline that studies issues of public hygiene, sanitary protection of the territories, being for the most part an epidemiological phenomenon and an element of epidemiology, has maintained historically developed attribute “sanitary”. Demonstrated is the fact that variations in interpretation of the terms in the sphere of sanitary protection of the territories in various contexts of international intercourse (WHO and SIC) do not affect general concept of the issue and choice of ways for handling a problem as regards provision of sanitary-epidemiological welfare of the population. Objectives and content of the two notions formalized in IHR (2005), – “global epidemiological surveillance” plus “response measures” – predetermine their equivalence (in reference to the situations covered in the document), to the definitions “epidemiological surveillance” plus “sanitary protection”, applied to in the territory of CIS counties.